Besit waardes rigtinggewend-normatiewe waarde? ’n Beoordeling van die Noordwes-Universiteit se waardeprojek - Walt, Barend Johannes van der (Koers, 2010)
Do values contain directional-normative value? A review of the value project of the North-West University As indicated in the title, the aim of this article is to determine the value (if any) of values, especially as expressed by a valuedriven institution. To avoid abstract reflection, the article (cf. the subtitle) focuses on a specific institution, viz. a university. To concretesise the investigation even more, the North-West University (which came into existence in 2004) is taken as a case study. The investigation develops as follows: by way of introduction, attention is first given to the popularity of present value thinking, followed by the problem statement: Are such values really capable of indicating a normative direction? Secondly, the development of a university with a normative foundation (the erstwhile Potchefstroom University for Christian Higher Education) towards a value-driven one (the new North-West University) is briefly described. In the third place a brief description of the NWU as a value-driven institution is given. Fourthly, attention is given to some practical problems which surfaced during the implementation of the value project. Fifthly, six theoretical-philosophical problems regarding the NWU’s value system are discussed. The next main point consists of a brief description from a reformational perspective (of structure, direction and relevance) of what an academic institution ought to be. Apart from expressing doubt about the real value of values to give a solid foundation and clear direction to a university, the preliminary conclusion also suggests further philosophical reflection on the real nature, status and authority of values.